2008
DOI: 10.1080/01443610801975870
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated appendices epiploicae through the posterior vaginal defect secondary to a ring pessary

Abstract: A 20-year-old woman was referred to the early pregnancy assessment unit (EPAU) by her GP, with 3 months amenorrhoea and spotting per vaginam. She had a complete miscarriage in 2004 and normal vaginal delivery in January 2006. She had continued to have irregular vaginal bleeding since her last childbirth. She was not using any contraception and her pregnancy test was negative 2 months before presenting to her GP. Trans-abdominal ultrasound scan revealed a slightly bulky uterus with no gestational sac and severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Thirteen papers discussed complications related to pessary size. [20][21][22][23][24][25][26][27][28][29][30][31] By combining the data in both case reports and case studies, we found that the most frequent complications were: vaginal discharge, bleeding, vesicovaginal fistula, erosion, ulceration, and foul odor (Table 1). We graded the reported complications using the Clavien-Dindo classification (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen papers discussed complications related to pessary size. [20][21][22][23][24][25][26][27][28][29][30][31] By combining the data in both case reports and case studies, we found that the most frequent complications were: vaginal discharge, bleeding, vesicovaginal fistula, erosion, ulceration, and foul odor (Table 1). We graded the reported complications using the Clavien-Dindo classification (Table 3).…”
Section: Resultsmentioning
confidence: 99%